SiO2-coated lead halide perovskites core–shell and their applications: a mini-review - Cuc Kim Trinh; Zubair Ahmad (Royal Society Open Science, 2024)
Research on lead halide perovskites has demonstrated that they are one of the potential materials for optoelectronic and bio-related applications owing to their promising optical and electronic properties. However, their poor chemical stability in ambient environments is a critical factor that affects their practical applications. Silica is known for its excellent environmental/chemical stability and good optical properties. Therefore, SiO2-coated lead halide perovskites have been studied by introducing the protective layer containing SiO2 to prevent the rapid destruction of their surface chemistry and environmental degradation. It is found that lead halide perovskite core–shell can significantly improve the stability and preserve their high photoluminescence quantum yield. In addition, controlling the shell thickness is also important to produce effective and suitable inorganic halide perovskites core–shell for practical applications. This mini-review discusses the stability, synthesis method and applications of SiO2-coated lead halide perovskite core–shell. Furthermore, the effect of the SiO2 shell thickness on lead halide perovskite core–shell-based applications is also reviewed.